Predictors of health-related quality of life in outpatients with coronary heart disease - Frøjd, Lars Aastebøl; Munkhaugen, John; Papageorgiou, Costas; Sverre, Elise; Moum, Torbjørn; Dammen, Toril (Frontiers in Psychology, 2023)
Health-related quality of life (HRQoL) is an important treatment target in patients with coronary heart disease (CHD) and is associated with poor outcomes. Therefore, it is of clinical importance to identify the key determinants of HRQoL among these patients. There is, however, limited knowledge of how a comprehensive set of psychosocial factors influence HRQoL. We aimed to determine the relative associations of clinical and psychosocial factors with mental and physical components of HRQoL in a sample of CHD outpatients. This cross-sectional study included 1042 patients 2-36 (mean 16) months after a CHD event recruited from two general Norwegian hospitals with a combined catchment area making up 7% of the Norwegian population, representative with regards to demographic and clinical factors. We collected data on HRQoL, demographics, comorbidities, coronary risk factors, and psychosocial factors. HRQoL was assessed using the Short Form 12 (SF12), which comprises a Mental Component Scale (MCS) and the Physical Component Scale (PCS). Crude and multi-adjusted linear regression analyses were used to investigate the association between covariates and MCS and PCS. Mean age was 61 (standard deviation [SD] 10) years, 20 % were females, 18% had type D personality, 20% significant depression symptoms, 14% significant symptoms of anxiety whereas 45% reported insomnia. The presence of type D personality (β:-.19), significant symptoms of depression (β:-.15), and the presence of insomnia (β:-.13) were negatively associated with MCS, but not PCS in multi-adjusted analyses. The presence of chronic kidney disease (β:-.11) was associated with reduced MCS, whereas the presence of chronic obstructive pulmonary disease (β:-.08) and low physical activity (β:-.14) were negatively associated with PCS. Younger age was associated with lower MCS, whereas older age was associated with lower PCS. We conclude that Type D personality, depressive symptoms, insomnia, and chronic kidney disease were the strongest determinants of the mental component of HRQoL. Assessing and managing these psychological factors among CHD outpatients may improve their mental HRQoL.